Baleen Whale Occurrence in the Waters Off Virginia and North Carolina, U.S.A. From 2001 to 2019 - Sarah D. Mallette; William A. McLellan; D. Ann Pabst; M. Louise Burt; Ryan J. McAlarney; Gwendolyn G. Lockhart; Erin W. Cummings; Joel T. Bell; Matthew B. Ogburn; Philip K. Hamilton; Andrew J. Read; Robert L. Brownell; et al. (Marine Mammal Science, 2026)
Eighteen years of visual survey and strandings data were used to describe baleen whale occurrence along the continental shelf of Virginia and North Carolina, U.S.A. This region experiences heavy anthropogenic use, which poses risks for mortality and injury to baleen whales. Between 2001 and 2019, six species of baleen whales were recorded, and whales occurred year‐round. The total number of (on‐ and off‐effort) sightings and strandings amounted to 838 whales, including humpback ( Megaptera novaeangliae , n = 503) , fin ( Balaenoptera physalus , n = 197) , North Atlantic right ( Eubalaena glacialis , NARW, n = 76 ), common minke ( B. acutorostrata , n = 51), sei ( B. borealis , n = 10), and blue ( B. musculus , n = 1) whales. Spatial modeling and abundance estimates indicated whale density and distribution changed seasonally. The highest densities of all whales combined occurred in winter and spring. Across seasons, average densities were highest in the northern portion of the study area. Ninety percent of NARW sightings were outside the designated Seasonal Management Areas in place for their protection. The stranding record offered a complementary view of species richness and seasonality. This study provides a baseline of baleen whale occurrence in an area experiencing increasing anthropogenic pressures (e.g., ship traffic and offshore wind‐energy development).

Stock Identity of Stranded Tamanend's Bottlenose Dolphins ( Tursiops erebennus ) With Evidence of Fisheries Interaction in Virginia, North Carolina, and South Carolina, 1996–2019 - Kim W. Urian; Susan G. Barco; Karen L. Clark; Alex M. Costidis; Paul Doshkov; Marina Piscitelli‐Doshkov; Alexandra L. Epple; Tiffany F. Keenan; William A. McLellan; Wayne E. McFee; D. Ann Pabst; Keith A. Rittmaster; et al. (Marine Mammal Science, 2026)
The complex population structure of Tamanend's bottlenose dolphins ( Tursiops erebennus ) along the U.S. Mid‐Atlantic coast complicates assessment of their bycatch. To improve our understanding of the stock identity of individual dolphins taken as bycatch in this region, we compared images of the dorsal fins of bottlenose dolphins that stranded with evidence of fishery interactions (FI+) to the Mid‐Atlantic Bottlenose Dolphin Catalog (MABDC). We obtained stranding data from NOAA Fisheries for 715 FI+ bottlenose dolphins from Virginia (VA), North Carolina (NC), and South Carolina (SC) from 1996 to 2019; approximately two thirds of these records included dorsal fin images. For records for which images were available, we applied restrictive criteria for image quality and dorsal fin distinctiveness and compared the remaining 145 distinctive FI+ individuals to the MABDC. We matched 18 dolphins to regional catalogs and assigned stock identity to 13 of the matches; two were from migratory coastal stocks and 11 were from small estuarine stocks in NC and SC. Our analysis demonstrates how the risk of bycatch varies across bottlenose dolphin stocks along the Mid‐Atlantic coast, provides an important feedback information loop to stranding responders and researchers studying dolphins in the field, and informs conservation efforts to address bycatch of bottlenose dolphins in this region.

Wastewater surveillance of SARS-CoV-2 and influenza in a dynamic university community: understanding how wastewater measurements correspond to reported cases - Matthew J. Jones; Rukayya Ibrahim; Shirley Clark; Yolanda M. Brooks; Heather E. Preisendanz; Thomas L. Richard; Andrew F. Read; Courtney J. Robinson; Samina Noorali; Michael J. Shreve; Nina L. Dennington; Justin D. Silverman; et al. (Science of The Total Environment, 2025)

Active interactions between animals and technology: biohybrid approaches for animal behaviour research - M. Papadopoulou; M. Ball; P. Bartashevich; A.L.J. Burns; V. Chiara; M.A. Clark; B.R. Costelloe; M. Fele; F. French; S. Hauert; M.K. Heinrich; J.E. Herbert-Read; et al. (Animal Behaviour, 2025)

Site‐Specific Nutrient Data Reveal the Importance of Soils in Driving the Mycorrhizal Make‐Up of Woody Vegetation Worldwide - Xiaobin Hua; Christopher H. Lusk; Ian A. Dickie; Stephen Adu‐Bredu; Kathryn J. Allen; Viviana Araus; Laurent Augusto; Pavel Barsukov; David Bauman; Félix Brédoire; David F. R. P. Burslem; James W. Dalling; et al. (Global Ecology and Biogeography, 2025)
Aim Arbuscular mycorrhizas (AM) and ectomycorrhizas (ECM) have different impacts on nutrient cycling, carbon storage, community dynamics and enhancement of photosynthesis by rising CO 2 . Recent global analyses have concluded that patterns of AM/ECM dominance in forests worldwide are shaped by climate, with soil nutrients contributing negligible additional explanatory power. However, their reliance on nutrient data from GIS surfaces masks important local influences of parent material, topography and soil age on soil nutrient status. We asked if use of site‐specific nutrient data reveals a more important role for nutrients. Time Period Present day. Location Global dataset comprising 703 sites, encompassing forests, savanna/woodlands, shrublands and deserts on all continents except Antarctica. Taxa Studied Arborescent plants, including angiosperms, gymnosperms and tree ferns. Methods Generalised Additive Models for Location, Scale and Shape (GAMLSS) to determine the effects of climate variables, soil nitrogen and soil phosphorus on the proportional representation of ECM and of non‐mycorrhizal species (NM) in woody vegetation. Results GAMLSS showed a strong negative relationship of ECM representation with mean annual temperature (MAT), and a strong negative relationship with soil total nitrogen. NM representation was highest on dry sites and phosphorus‐poor sites. Reanalysis showed that GIS‐derived soil nutrient data had less explanatory power than site‐specific nutrient data, and resulted in poorer model fits. Conclusions Our results support the long‐held belief that soil nutrients as well as climate influence the relative fitness of different mycorrhizal syndromes worldwide, and demonstrate the value of using site‐specific nutrient data. Soil nutrients should be considered when predicting the impact of climate change on the mycorrhizal composition of vegetation and resulting shifts in ecosystem processes.

Dissemination and persistence of antimicrobial resistance (AMR) along the wastewater-river continuum - Daniel S. Read; H. Soon Gweon; Michael J. Bowes; Muna F. Anjum; Derrick W. Crook; Kevin K. Chau; Liam P. Shaw; Alasdair Hubbard; Manal AbuOun; Holly J. Tipper; Sarah J. Hoosdally; Mark J. Bailey; et al. (Water Research, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Havens are a pathway, not an endpoint, for species recovery: A response to Woinarski et al. (2023) - John L. Read; Kev Bradley; Iain J. Gordon; Adrian D. Manning; Linda E. Neaves; April E. Reside; Kiarrah J. Smith; Rick Southgate; Adrian F. Wayne; Andrew R. Weeks; Belinda A. Wilson; Katherine E. Moseby (Biological Conservation, 2023)

Hypoxia Interrupts the Secondary Production Service Provided by Oyster Reef Macrofauna in Mississippi Sound, USA - Chet F. Rakocinski; J. Read Hendon; Kathy E. VanderKooy; Jeremy M. Higgs; Virginia R. Schweiss; Scott C. McIntosh; Daneen P. Menke (Estuaries and Coasts, 2023)

Exploring movement patterns and changing distributions of baleen whales in the western North Atlantic using a decade of passive acoustic data - Genevieve E. Davis; Mark F. Baumgartner; Peter J. Corkeron; Joel Bell; Catherine Berchok; Julianne M. Bonnell; Jacqueline Bort Thornton; Solange Brault; Gary A. Buchanan; Danielle M. Cholewiak; Christopher W. Clark; Julien Delarue; et al. (Global Change Biology, 2020)
Six baleen whale species are found in the temperate western North Atlantic Ocean, with limited information existing on the distribution and movement patterns for most. There is mounting evidence of distributional shifts in many species, including marine mammals, likely because of climate‐driven changes in ocean temperature and circulation. Previous acoustic studies examined the occurrence of minke ( Balaenoptera acutorostrata ) and North Atlantic right whales (NARW; Eubalaena glacialis ). This study assesses the acoustic presence of humpback ( Megaptera novaeangliae ), sei ( B. borealis ), fin ( B. physalus ), and blue whales ( B. musculus ) over a decade, based on daily detections of their vocalizations. Data collected from 2004 to 2014 on 281 bottom‐mounted recorders, totaling 35,033 days, were processed using automated detection software and screened for each species' presence. A published study on NARW acoustics revealed significant changes in occurrence patterns between the periods of 2004–2010 and 2011–2014; therefore, these same time periods were examined here. All four species were present from the Southeast United States to Greenland; humpback whales were also present in the Caribbean. All species occurred throughout all regions in the winter, suggesting that baleen whales are widely distributed during these months. Each of the species showed significant changes in acoustic occurrence after 2010. Similar to NARWs, sei whales had higher acoustic occurrence in mid‐Atlantic regions after 2010. Fin, blue, and sei whales were more frequently detected in the northern latitudes of the study area after 2010. Despite this general northward shift, all four species were detected less on the Scotian Shelf area after 2010, matching documented shifts in prey availability in this region. A decade of acoustic observations have shown important distributional changes over the range of baleen whales, mirroring known climatic shifts and identifying new habitats that will require further protection from anthropogenic threats like fixed fishing gear, shipping, and noise pollution.

Bioengineering a Future Free of Marine Plastic Waste - Maya U. Sheth; Sarah K. Kwartler; Emma R. Schmaltz; Sarah M. Hoskinson; E. J. Martz; Meagan M. Dunphy-Daly; Thomas F. Schultz; Andrew J. Read; William C. Eward; Jason A. Somarelli (Frontiers in Marine Science, 2019)

Survey of Citrus tristeza virus (CTV) on Citrus paradisi (Macfad.) cv. “Marsh” in South Africa - D. A. Read; M. F. Palacios; J. Figueroa; B. Stein; G. Pietersen (European Journal of Plant Pathology, 2018)

Survey of Citrus tristeza virus (CTV) diversity in pigmented Citrus x paradisi (Macfad.) (Grapefruit) trees in north-western Argentina - D. A. Read; M. F. Palacios; J. Kleynhans; J. Figueroa; L. Foguet; B. Stein; G. Pietersen (European Journal of Plant Pathology, 2018)

Resilience of harbor porpoises to anthropogenic disturbance: Must they really feed continuously? - Jeroen P. A. Hoekendijk; Jerome Spitz; Andrew J. Read; Mardik F. Leopold; Michael C. Fontaine (Marine Mammal Science, 2018)

Survey of citrus tristeza virus (CTV) strains in Citrus x limon (L) Burm f. (lemon) in Tucumán Province, Argentina - D. A. Read; M. F. Palacios; J. Figueroa; L. Foguet; J. Kleynhans; B. Stein; G. Pietersen (European Journal of Plant Pathology, 2017)

Projected shifts in fish species dominance in Wisconsin lakes under climate change - Gretchen J. A. Hansen; Jordan S. Read; Jonathan F. Hansen; Luke A. Winslow (Global Change Biology, 2017)
Temperate lakes may contain both coolwater fish species such as walleye ( Sander vitreus ) and warmwater fish species such as largemouth bass ( Micropterus salmoides ). Recent declining walleye and increasing largemouth bass populations have raised questions regarding the future trajectories and management actions for these species. We developed a thermodynamic model of water temperatures driven by downscaled climate data and lake‐specific characteristics to estimate daily water temperature profiles for 2148 lakes in Wisconsin, US , under contemporary (1989–2014) and future (2040–2064 and 2065–2089) conditions. We correlated contemporary walleye recruitment and largemouth bass relative abundance to modeled water temperature, lake morphometry, and lake productivity, and projected lake‐specific changes in each species under future climate conditions. Walleye recruitment success was negatively related and largemouth bass abundance was positively related to water temperature degree days. Both species exhibited a threshold response at the same degree day value, albeit in opposite directions. Degree days were predicted to increase in the future, although the magnitude of increase varied among lakes, time periods, and global circulation models ( GCM s). Under future conditions, we predicted a loss of walleye recruitment in 33–75% of lakes where recruitment is currently supported and a 27–60% increase in the number of lakes suitable for high largemouth bass abundance. The percentage of lakes capable of supporting abundant largemouth bass but failed walleye recruitment was predicted to increase from 58% in contemporary conditions to 86% by mid‐century and to 91% of lakes by late century, based on median projections across GCM s. Conversely, the percentage of lakes with successful walleye recruitment and low largemouth bass abundance was predicted to decline from 9% of lakes in contemporary conditions to only 1% of lakes in both future periods. Importantly, we identify up to 85 resilient lakes predicted to continue to support natural walleye recruitment. Management resources could target preserving these resilient walleye populations.

Genomewide investigation of adaptation to harmful algal blooms in common bottlenose dolphins ( Tursiops truncatus ) - Kristina M. Cammen; Thomas F. Schultz; Patricia E. Rosel; Randall S. Wells; Andrew J. Read (Molecular Ecology, 2015)
Harmful algal blooms ( HAB s), which can be lethal in marine species and cause illness in humans, are increasing worldwide. In the Gulf of Mexico, HAB s of Karenia brevis produce neurotoxic brevetoxins that cause large‐scale marine mortality events. The long history of such blooms, combined with the potentially severe effects of exposure, may have produced a strong selective pressure for evolved resistance. Advances in next‐generation sequencing, in particular genotyping‐by‐sequencing, greatly enable the genomic study of such adaptation in natural populations. We used restriction site‐associated DNA ( RAD ) sequencing to investigate brevetoxicosis resistance in common bottlenose dolphins ( Tursiops truncatus ). To improve our understanding of the epidemiology and aetiology of brevetoxicosis and the potential for evolved resistance in an upper trophic level predator, we sequenced pools of genomic DNA from dolphins sampled from both coastal and estuarine populations in Florida and during multiple HAB ‐associated mortality events. We sequenced 129 594 RAD loci and analysed 7431 single nucleotide polymorphisms ( SNP s). The allele frequencies of many of these polymorphic loci differed significantly between live and dead dolphins. Some loci associated with survival showed patterns suggesting a common genetic‐based mechanism of resistance to brevetoxins in bottlenose dolphins along the Gulf coast of Florida, but others suggested regionally specific mechanisms of resistance or reflected differences among HAB s. We identified candidate genes that may be the evolutionary target for brevetoxin resistance by searching the dolphin genome for genes adjacent to survival‐associated SNP s.

Ecological niche segregation among five toothed whale species off the NW Iberian Peninsula using ecological tracers as multi-approach - Paula Méndez-Fernandez; Graham J. Pierce; Paco Bustamante; Tiphaine Chouvelon; Marisa Ferreira; Angel F. González; Alfredo López; Fiona L. Read; M. Begoña Santos; Jérôme Spitz; José V. Vingada; Florence Caurant (Marine Biology, 2013)

Phytoplankton distribution and nitrogen dynamics in the southwest indian subtropical gyre and Southern Ocean waters - S. J. Thomalla; H. N. Waldron; M. I. Lucas; J. F. Read; I. J. Ansorge; E. Pakhomov (Ocean Science, 2011)
During the 1999 Marion Island Oceanographic Survey (MIOS 4) in late austral summer, a northbound and reciprocal southbound transect were taken along the Southwest Indian and Madagascar Ridge, between the Prince Edward Islands and 31° S. The sections crossed a number of major fronts and smaller mesoscale features and covered a wide productivity spectrum from subtropical to subantarctic waters. Associated with the physical survey were measurements of size fractionated chlorophyll, nutrients and nitrogen (NO3, NH4 and urea) uptake rates. Subtropical waters were characterised by low chlorophyll concentrations (max = 0.27.3 mg m−3 dominated by pico-phytoplankton cells (> 81%) and very low f-ratios (

Measurement and calculation of OH reactivity at a United Kingdom coastal site - James D. Lee; Jennifer C. Young; Katie A. Read; Jacqueline F. Hamilton; James R. Hopkins; Alastair C. Lewis; Brian J. Bandy; James Davey; Peter Edwards; Trevor Ingham; Daniel E. Self; Shona C. Smith; et al. (Journal of Atmospheric Chemistry, 2009)

Abnormal gonadal morphology in intersex, Echinogammarus marinus (Amphipoda): a possible cause of reduced fecundity? - A. T. Ford; T. P. Rodgers-Gray; I. M. Davies; A. M. Dunn; P. A. Read; C. D. Robinson; J. E. Smith; T. F. Fernandes (Marine Biology, 2005)

Abnormal gonadal morphology in intersex, Echinogammarus marinus (Amphipoda): a possible cause of reduced fecundity? - A. T. Ford; T. P. Rodgers-Gray; I. M. Davies; A. M. Dunn; P. A. Read; C. D. Robinson; J. E. Smith; T. F. Fernandes (Marine Biology, 2005)

The effect of a pathogen epidemic on the genetic structure and reproductive strategy of the crustacean Daphnia magna - Suzanne E. Mitchell; Andrew F. Read; Tom J. Little (Ecology Letters, 2004)
Host–parasite coevolution is potentially of great importance in producing and maintaining biological diversity. However, there is a lack of evidence for parasites directly driving genetic change. We examined the impact of an epidemic of the bacterium Pasteuria ramosa on a natural population of the crustacean Daphnia magna through the use of molecular markers (allozymes) and laboratory experiments to determine the susceptibility of hosts collected during and after the epidemic. Some allozyme genotypes were more heavily infected than others in field samples, and the population genetic structure differed during and after the epidemic, consistent with a response to parasite‐mediated selection. Laboratory studies showed no evidence for the evolution of higher resistance, but did reveal an intriguing life‐history pattern: host genotypes that were more susceptible also showed a greater tendency to engage in sex. In light of this, we suggest a model of host–parasite dynamics that incorporates the cycles of sex and parthenogenesis that Daphnia undergo in the field.

Evaluation in barley lines of a simple pollen method for breeding for drought tolerance in wheat - James M. Morgan; John F. Holland; Barbara J. Read (Cereal Research Communications, 2002)

Phenylalanine kinetics are associated with tardive dyskinesia in men but not in women - M. A. Richardson; Margaret A. Reilly; Laura L. Read; Cheryl J. Flynn; Raymond F. Suckow; Timothy J. Maher; Istvan Sziraki (Psychopharmacology, 1999)

Branched chain amino acids decrease tardive dyskinesia symptoms - M. A. Richardson; Margaret L. Bevans; Josephine B. Weber; Janet J. Gonzalez; Cheryl J. Flynn; Leora Amira; Laura L. Read; Raymond F. Suckow; Timothy J. Maher (Psychopharmacology, 1999)